First record of the genus Oxyrrhexis Foerster, 1869 (Hymenoptera: Ichneumonidae: Pimplinae, Ephialtini) for the fauna of Egypt, with an unexpected new host record - Gadallah, Neveen S.; El-Hennawy, Hisham K. (Zootaxa, 2017)
Oxyrrhexis Foerster, 1869 of the Polysphincta genus-group, is recorded for the first time for the Egyptian fauna, with one species, O. carbonator (Gravenhorst, 1807). Specimens have been reared from the titanoecid spider Nurscia albomaculata (Lucas, 1846), which represents a new host record for O. carbonator as well as for the Polysphincta genus-group as a whole.